Effects of the COVID-19 Pandemic on Students and their Parents - Graumann , Olga (International Dialogues on Education Journal, 2020)
The COVID-19 pandemic resulted in school closures in spring 2020 in many countries, including Germany, to stem the spread of the virus. From one day to the next, school learning became the responsibility of parents, and school administrators expected teachers in all types of schools to switch from almost exclusively analogue teaching to distance learning – in particular to digitalized teaching – from one day to the next. In this article we analyze what this means for families. It is shown that the inequality of opportunities in education is increased when schools and families lack digital equipment and expanded Internet connections. It describes the problems that parents and children have had and will continue to have with immature and unproven concepts of distance learning, since schools in Germany are far from making up for the deficit in the area of digitized instruction. The state of emergency in the time of a pandemic also clearly shows the limits of innovative teaching with the new media and raises awareness of the importance of an intensive analogue pedagogical teacher-pupil relationship.